Inverse association of daily fermented soybean paste (“Jang”) intake with metabolic syndrome risk, especially body fat and hypertension, in men of a large hospital-based cohort - Jeong, Su-Ji; Yang, Hee-Jong; Yang, Hee Gun; Ryu, Myeong Seon; Ha, Gwangsu; Jeong, Do Yeon; Park, Sunmin (Frontiers in Nutrition, 2023)
Jang is a fermented soybean paste containing salt and is traditionally used as a substitute for salt to enhance the flavor of foods in Korea. It has been speculated that regular consumption of Jang may lower the risk of metabolic syndrome(MetS). We hypothesized that Jang intake was associated with the risk of MetS and its components after adjusting for potential confounders, including sodium intake. The hypothesis was investigated according to gender in a large city hospital-based cohort(n=58,701) in Korea. Jang intake, calculated as the sum of the intakes of Chungkookjang, Doenjang, Doenjang soup, and Ssamjang(a mixture of Doenjang and Kochujang), was included in the semi-quantitative food frequency questionnaire(SQFFQ) administered to the cohort, and the daily Jang intake was estimated. The participants were categorized into low-Jang and high-Jang groups by 1.9 g daily Jang intake. MetS was defined according to the 2005 revised US National Cholesterol Education Program-Adult Treatment Panel III(NCEP-ATP III) criteria modified for Asians. The participants in the low-Jang and high-Jang groups consumed about an average of 0.63 g and 4.63 g Jang daily; their total sodium intake was about 1.91 and 2.58 g/day, respectively. The participants in the high-Jang group had higher energy, fiber, calcium, vitamin C, vitamin D, and potassium intake than those in the low-Jang group. After adjusting for covariates, the participants with the highest sodium intake(≥3.31 g/day) were positively associated with MetS risk in the quintiles of men and women. Among the MetS components, waist circumference, fat mass, and hypo-high-density lipoprotein(HDL)-cholesterolemia were positively associated with sodium intake in all participants and women. Unlike the association seen with sodium intake, Jang intake(≥1.9 g/day) was inversely associated with MetS components, including waist circumference, fat mass, serum glucose concentrations, and hypo-HDL-cholesterolemia in all participants and men, after adjusting for covariates including sodium intake. In conclusion, substituting salt for Jang in cooking along with reducing total sodium intake may be recommended to prevent and alleviate MetS incidence, and its efficacy for MetS was better in men than women. The results can be applied to sodium intake in Asian countries where salt is used to promote flavor.